Plasmonic-based platforms for diagnosis of infectious diseases at the point-of-care - Li, Zihan; Leustean, Luca; Inci, Fatih; Zheng, Min; Demirci, Utkan; Wang, Shuqi (Biotechnology advances, 2019)
Infectious diseases such as HIV-1/AIDS, tuberculosis (TB), hepatitis B (HBV), and malaria still exert a tremendous health burden on the developing world, requiring rapid, simple and inexpensive diagnostics for on-site diagnosis and treatment monitoring. However, traditional diagnostic methods such as nucleic acid tests (NATs) and enzyme linked immunosorbent assays (ELISA) cannot be readily implemented in point-of-care (POC) settings. Recently, plasmonic-based biosensors have emerged, offering an attractive solution to manage infectious diseases in the developing world since they can achieve rapid, real-time and label-free detection of various pathogenic biomarkers. Via the principle of plasmonic-based optical detection, a variety of biosensing technologies such as surface plasmon resonance (SPR), localized surface plasmon resonance (LSPR), colorimetric plasmonic assays, and surface enhanced Raman spectroscopy (SERS) have emerged for early diagnosis of HIV-1, TB, HBV and malaria. Similarly, plasmonic-based colorimetric assays have also been developed with the capability of multiplexing and cellphone integration, which is well suited for POC testing in the developing world. Herein, we present a comprehensive review on recent advances in surface chemistry, substrate fabrication, and microfluidic integration for the development of plasmonic-based biosensors, aiming at rapid management of infectious diseases at the POC, and thus improving global health.